Games of mathematical content "Funny Geometry" as a means of developing logical thinking in preschool children - Plugatoriova V. A., Nazarova E. B., Goncharova S. F. (Educational environment today: development strategy, 2023)
Work experience in the use of the "Geometric Blanket" manual by kindergarten teachers as part of the implementation of the "Cheerful Geometry" project in educational work with preschool children.
Keywords: финансовая грамотность; критическое мышление; дети дошкольного возраста; логическое мышление; математические представления; critical thinking; preschool children; logical thinking; financial literacy; федеральная образовательная программа; federal educational program; mathematical representations